Responsabilidad social de las cooperativas de Ahorro y Crédito en el Sur del D.M. de Quito y su aporte a la economía popular y solidaria; Caso, Cooperativa de Ahorro y Crédito Comunidad Empresarial para el desarrollo económico y social (CEDES) LTDA. - Lanchi Cárdenas, Ángel (2014)
To determine the contributions of cooperatives credit unions in the popular and solidarity economy as part of their social responsibility to support development and economic empowerment of its members in southern Quito DM, taking as a case study the Credit Union Community Business Credit for Economic and Social Development (CEDES) LTDA.